Investigation of the recyclability of applications involving MgO cement - Lim, Chin Haow (2016)
Ordinary Portland Cement (OPC) is the most popular binder used in construction industry. However, the manufacturing process of OPC has led to some negative environmental impacts, therefore a more environmental friendly alternative to OPC is most welcomed. Reactive MgO cement has been considered a serious contender in this regard as it has a lower clinkering temperature, ability to sequester CO2 in the curing process and can be fully recycled when it is used as the only binder for cement product through calcination.